ズワイガニ ノ キンニクシツ オヨビ カンスイゾウ チュウシュツ エキ ノ カスイ ブンカイ ゼンゴ ニオケル アミノサン リョウ ノ ヘンカ - 宮川, 正美; ミヤガワ, マサヨシ; 久城, 達也; クシロ, タツヤ; 井上, 裕二; イノウエ, ユウジ; Miyagawa, Masayashi; Kushiro, Tatsuya; Inoue, Yuzi (鳥取大学教育学部, 1987)
departmental bulletin paper